Обзор вакцин против гриппа лошадей: прошлое, настоящее и будущее (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2025)
The article presents current data on the types of vaccines used in practical horse breeding. Inactivated whole-virion vaccines demonstrate high efficacy and safety. Subunit vaccines based on specific antigens provide a targeted immune response, minimizing adverse reactions. Live attenuated vaccines containing weakened virus strains lead to more pronounced immunity, but require careful monitoring. Among the promising areas, vector vaccines using carrier viruses to deliver genetic material are distinguished, which significantly enhances the immune response. Research in the field of equine influenza has led to the development of new experimental vaccines using genetically engineered methods. The technology of reverse genetics of influenza viruses makes it possible to obtain modified strains that serve as the basis for creating effective and safe vaccines.
Keywords: vaccine, strain, virus, influenza, horse